Spatio-Temporal Characteristics of Dengue Outbreaks - S. Reis, Saulo D.; Böttcher, Lucas; Nogueira, João P. da C.; Sousa, Geziel S.; Lima Neto, Antonio S.; Herrmann, Hans J.; Andrade, José S. (Frontiers in Physics, 2022)
Based on a data set of dengue cases in the Brazilian city of Fortaleza, collected from 2011 to 2016, we study the spatio-temporal characteristics of dengue outbreaks to characterize epidemic and non-epidemic years. First, we identify regions with a high incidence of dengue cases and mosquito larvae in different years and analyze their corresponding correlations. We find that the characteristic correlation length of the epidemic is of the order of the system size, suggesting that factors such as citizen mobility may play a significant role in driving the spatial spread of the disease. We also find that spatial correlations are substantially higher in epidemic years with a distribution skewed towards large values than in non-epidemic years. Inspired by this observation, we perform a mean-field estimation of the basic reproduction number and find that the estimated values agree well with the values reported for other regions in Brazil and other countries, pointing towards similar underlying spreading mechanisms. These findings provide insights into the spreading characteristics of dengue in densely populated areas and may be relevant for improving disease containment strategies.